Modeling Sectoral Investments, Output and Costs Using VAR Models - Калкабаева, Г.М.; Atabayeva А.К.; Kurmanalina А.K.; Forgo, A.T. (BUKETOV BUSINESS REVIEW, 2024)
Object: This paper examines the dynamics and structure of fixed capital investment, quantifying its impact on output and material costs in different sectors of the Kazakhstani economy. Method: Using empirical and statistical methods, the study explores sector-specific investments, while VAR models are developed to evaluate how investment affects output and material costs. Ordinary Least Squares (OLS) was employed to assess the interrelationships among variables. Model fit was evaluated using information criteria (AIC, BIC, HQIC) and t-statistics. Results: The analysis revealed imbalances in the sectoral distribution of fixed capital investment, with predominance in the non-productive sector. VAR modeling indicated that fixed capital investment exerted the most significant positive impact on output in the short term for the trade sector and in both the short and long terms for the manufacturing and mining industries. Conclusions: Our findings indicate that the impact of investment on different economic sectors is heterogeneous. In the short term, investments were found to reduce material costs only in the mining, construction, and transportation sectors, while in the long term, this effect was observed in agriculture and energy. The largest increase in output is expected in the trade and manufacturing sectors. The most significant growth in fixed capital investment is projected for the trade, manufacturing, construction, and agriculture sectors.